Optimization of Library Services at SMK Negeri 8 Makassar - Akadira, Tora; Jamaluddin, Jamaluddin; Sabir, Muhammad; Saleh, Sirajuddin (Pinisi Business Administration Review, 2022)
Library service is the provision of library material services owned by a library to library visitors or users who come to the library. The library is also defined as a container or place to store information where the information has various types and forms and is managed in accordance with the applicable or predetermined system. This research is a qualitative research with a descriptive type of research that aims to find out how to optimize library services at SMK Negeri 8 Makassar. The informants in this study were the head of the library, library staff, and 3 students of SMK Negeri 8 Makassar. Data collection techniques through observation methods, interview methods, and documentation methods. The data analyzed is data collected at the time of the study. Activities in data analysis are; data collection, data presentation, data condensation and conclusions. The results showed that library services at SMK Negeri 8 Makassar were categorized as optimal. Seeing the focus in this research, namely: Circulation services in the optimal category; Information services in the optimal category; tutoring services get results that are quite optimal.